Towards learner-centeredness: Motivational strategies in Lower-secondary English classes - Röhrichová, Veronika (Univerzita Pardubice, 2019)
The diploma thesis deals with motivational strategies in lower-secondary English classes in the learner-centred context. The paper is divided into two parts, theoretical and practical. Within the theoretical part, learner-centeredness and its factors are outlined, motivational theories in psychology and education are provided and subsequently, models of motivation within second language acquisition are discussed. Lastly, the theoretical part discusses motivational strategies within the process model of motivation and defines motivational strategies which are in accordance with learner-centeredness and which are suitable for lower-secondary English learners. The research in the practical part is conducted in the form of a case study. The aim of the research is to find out whether the teacher uses the defined motivational strategies, what strategies she uses and how she uses them. Moreover, the aim is to find out how the teacher and the learners perceive these strategies. Three research methods are used in the study: observation, interview and focus groups. The collected data are summarized, analysed and compared.
Motivační strategie jako prostředek ke zvýšení míry learner-centeredness v hodinách angličtiny na druhém stupni základní školya vnižších třídách víceletých gymnázií
Keywords: výuka zaměřená na žáka; motivace; motivační strategie; model motivace; případová studie; výuka anglického jazyka; learner-centeredness; motivation; motivational strategies; process model of motivation; case study; English language teaching